Design of an Epitope Candidate Vaccine Against Iha Protein in Escherichia Coli: an in Silico Approach: An Epitope Candidate Vaccine Against Escherichia Coli - Sefid , Fateme; Alagheband Bahrami , Armina; Rajabibazl , Masoumeh; Rahmati , Mohammad; payandeh, zahra; Kalantar , Seyed Mehdi; Dastmalchi , Siavoush; Nabi Afjadi, Mohsen (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Iron-regulated outer membrane virulence protein (IrgA) involved in the initial step of iron uptake by binding ferric- iron chelation siderophore that allows the bacterium to extract iron from the environment. IrgA homologue adhesion (Iha) revealed as a novel adherence conferring molecule. In this study, homology modeling, fold recognition and Ab-initio approaches along with their combination were invoked to determine the tertiary structure of Iha. Material and Methods: Specific bioinformatics methods were used to forecast their immunological, biochemical and functional properties. Results: The results showed that IrgA constitutes beta barrel structures. The immunological, biochemical and functional analyzes led us to pick a region of every antigen with the highest immunogenic properties. Comparison of antigenicity scores for selected regions and the whole proteins showed that the antigenicity of the selected regions is considerably higher than the whole antigen. Conclusion: Our strategy for prediction of the 3D structure and epitopes could be deemed as an amenable approach for efficient vaccine design. These approaches used could provide the basis for future functional studies to design and development of a suitable vaccine. In this regard, a region includes residues 200-340, covering a part of barrel, was chosen as vaccine candidate against Iha protein in Escherichia Coli.